Fostering Educational Excellence: Differentiated Instruction in Teaching English in Kurikulum Merdeka Towards SDGs 2030 - Siti Khasinah (Bansigom Na Publisher, 2025)
This paper examines the role of Differentiated Instruction (DI) in Kurikulum Merdeka and its contribution to SDG 4: Quality Education. DI addresses students' diverse needs, interests, and readiness by customizing content, processes, products, and learning environments. It aligns with student-centered learning and Profil Pelajar Pancasila, promoting creativity, independence, and adaptability. Key components of DI include content differentiation, process variation, product customization, and inclusive learning environments. Challenges like limited time, resources, and teacher readiness are acknowledged, with solutions such as gradual implementation, leveraging technology, and fostering teacher collaboration through professional learning communities. Reflective practice and ongoing professional development are emphasized to enhance teachers' instructional strategies. The paper highlights DI’s contribution to SDG 10 by reducing educational inequalities. Presented during an international community engagement program, the study underscores global collaboration's role in advancing academic quality. By adopting DI, educators create inclusive, equitable, and impactful learning environments, supporting the achievement of SDGs 2030 and preparing students for a dynamic world.